Lovie : The Story of a Southern Midwife and an Unlikely Friendship - Yarger, Lisa (Book collections on Project MUSE., 2016)
From 1950 until 2001, Lovie Beard Shelton practiced midwifery in eastern North Carolina homes, delivering some 4,000 babies to black, white, Mennonite, and hippie women; to those too poor to afford a hospital birth; and to a few rich enough to have any kind of delivery they pleased. This is a provocative chronicle of Shelton's life and work, which spanned enormous changes in midwifery and in the ways women give birth"--